2022
DOI: 10.1111/apt.17252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time to pre‐emptive transjugular intrahepatic portosystemic shunt on patient outcome, a UK multicentre cohort study

Abstract: Summary Background Pre‐emptive transjugular intrahepatic portosystemic shunt (pTIPSS) should be considered within 72 hours following acute oesophageal variceal bleeding. However, recent studies highlight the difficulty in providing pTIPSS within this narrow timeframe. Delaying pTIPSS beyond 72 hours has not been studied. Aim To determine if the time taken to perform pTIPSS alters patient outcome. Method Patients referred to 4 UK tertiary centres for pTIPSS between 01 January 2010 and 31 December 2018 were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…This suggests that delaying interventions will likely result in selecting patients with better spontaneous survival, which can lead to survival bias in clinical trials. Recent studies have suggested that delaying p-TIPS placement until 28 days after admission may result in even greater survival benefits than placing p-TIPS within 72 hours of admission 28 . However, our results show that any intervention applied to patients who have already survived will be associated with better survival.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This suggests that delaying interventions will likely result in selecting patients with better spontaneous survival, which can lead to survival bias in clinical trials. Recent studies have suggested that delaying p-TIPS placement until 28 days after admission may result in even greater survival benefits than placing p-TIPS within 72 hours of admission 28 . However, our results show that any intervention applied to patients who have already survived will be associated with better survival.…”
Section: Discussioncontrasting
confidence: 65%
“…Recent studies have suggested that delaying p-TIPS placement until 28 days after admission may result in even greater survival benefits than placing p-TIPS within 72 hours of admission. [28] However, our results show that any intervention applied to patients who have already survived will be associated with better survival. For example, a patient who was initially classified as Child C at admission would have much better survival if the decision for a p-TIPS is delayed for 3 weeks.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, as mentioned in the Baveno VII consensus, it is necessary to assess whether pTIPS performed outside the 72-h window is still effective and safe [ 5 ]. Dunne P et al compared the clinical outcomes of early pTIPS (<72 h) and late pTIPS (72h-28 days) and similar short- and long-term survival benefits between the two groups were found [ 27 ]. The same results were observed in our study, but unlike the study conducted by Dunne P et al, we defined the time window for late pTIPS as 72 h-5d because the time frame for AVB is 5 d as defined by the Baveno consensus [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to liver and kidney function, this study indicated that the serum TB and DB levels of patients at 1 day – 1 month after TIPS were higher than those preoperatively, which may be associated with the transient injury of liver function brought about by TIPS surgery. TIPS allowed portal vein blood to enter the systemic circulation directly without passing through the liver parenchyma, thus aggravating hypoxia and ischemia in liver cells [26,27]. Subsequently, serum TB and DB decreased gradually and liver function improved, though bilirubin levels did not return to normal ranges 3 months after operation.…”
Section: Discussionmentioning
confidence: 99%